(untitled) (Baghdad Science Journal, 2025)
The present study aimed to determine the frequency of ABO and Rh blood group antigens among Sabians (Mandaeans) population. This paper document the frequency of ABO and Rh blood groups among the Sabians (Mandaeans) population of Iraq.There is no data available on the ABO/Rh (D) frequencies in the Sabians (Mandaeans) population. Total 341 samples analyzed; phenotype O blood type has the highest frequency 49.9%, followed by A 28.7%, and B 13.8% whereas the lowest prevalent blood group was AB 7.6%. The overall phenotypic frequencies of ABO blood groups were O>A>B>AB. The allelic frequencies of O, A, and B alleles were 0.687, 0.2 and 0.1122 respectively. Rhesus study showed that with a percentage of 96.2% Rh (D) positive is by far the most prevalent, while Rh (d) negative is present only in 3.8% of the total population. The Sabians (Mandaeans) ethnic group showed the same distribution of ABO and Rh blood groups with others ethnic groups in Iraqi population.